2004
DOI: 10.1063/1.1641183
|View full text |Cite
|
Sign up to set email alerts
|

Polarization relaxation anisotropy in Pb(Zn1/3Nb2/3)O3-PbTiO3 single-crystal ferroelectrics as a function of fatigue history

Abstract: Polarization relaxation was studied in Pb(Zn1/3Nb2/3)O3-PbTiO3 (PZN-PT) single crystals that show fatigue anisotropy. To excite prepoled crystals, a modest dc voltage (<1/2 of the coercive field) was applied along the poling direction. Upon removal of the voltage, the polarization decay in the time domain was measured. Experimental data were modeled with a stretched exponential function. Stretching exponent (β〈hkl〉) and characteristic time (τ〈hkl〉) constants for polarization relaxation were determined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…There are two major ways to improve the fatigue endurance of piezoelectricity. The first one is to keep the ceramic away from the MPB or PPT, which is not viable because it will result in a huge decrease in the piezoelectric response. , Furthermore, some previous works reported that ⟨001⟩ c -oriented rhombohedral ferroelectric materials show excellent fatigue resistance, whereas ⟨111⟩ c -oriented rhombohedral ferroelectric materials demonstrate a much poorer fatigue resistance. Therefore, for the piezoelectric materials with coexisting tetragonal–rhombohedral phases, the alternative approach is to control their orientation.…”
Section: Introductionmentioning
confidence: 99%
“…There are two major ways to improve the fatigue endurance of piezoelectricity. The first one is to keep the ceramic away from the MPB or PPT, which is not viable because it will result in a huge decrease in the piezoelectric response. , Furthermore, some previous works reported that ⟨001⟩ c -oriented rhombohedral ferroelectric materials show excellent fatigue resistance, whereas ⟨111⟩ c -oriented rhombohedral ferroelectric materials demonstrate a much poorer fatigue resistance. Therefore, for the piezoelectric materials with coexisting tetragonal–rhombohedral phases, the alternative approach is to control their orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that no significant difference exists in the polarization relaxation behavior of bulk material and that observed in thin films. 29,30 Similar to the thin films, in the bulk MAPBB crystal an initial drop of the polarization is observed which then levels out to a slow decrease, fitted by a stretched-exponential function.…”
Section: Discussionmentioning
confidence: 80%